Effects of education and social contact on mental health-related stigma among high-school students. (November 2019) - Lanfredi, Mariangela; Macis, Ambra; Ferrari, Clarissa; Rillosi, Luciana; Ughi, Elena Cadone; Fanetti, Agnese; Younis, Nadia; Cadei, Lorenza; Gallizioli, Caterina; Uggeri, Guido; Rossi, Roberta
Highlights: This study compared the effect of three different school-based anti-stigma programs on knowledge acquisition and attitudes about mental illness. All the three types of intervention - albeit to different extents - were effective in increasing knowledge, attitudes, empowerment, willingness to interact, and seeking help. Findings showed that an increase in knowledge is associated with an increase in positive attitudes toward people with mental illness. Positive changes in general attitudes toward mental illness was positively and significantly associated with willingness to interact and help-seeking intentions. Results encourage the use of anti-stigma interventions in order to decrease negative attitudes toward mental illness and improve behavioral intentions among adolescents. Abstract: Poor knowledge and stigma toward people with mental illness negatively affect intentions to seek help among adolescents. The study aimed to assess the impact of three school-based interventions and to explore whether positive changes in attitudes were linked to more favorable changes in desire for social distance and seeking help. A total of 221 upper secondary students were allocated to three interventions: 1. social contact; 2. Mental Health Literacy (MHL) conducted by clinicians; 3. MHL conducted by dis-peer instructors. Measures of knowledge, attitudes, views on empowerment and recovery, willingness to interact, and help seeking were collected. Generalized Estimating Equations and Structural Equation Modeling (SEM) were used to evaluate scores differences between interventions through time, and to test the interrelationships between knowledge, attitudes variables and the two outcomes of interest. Findings showed that all groups improved in knowledge, attitudes, empowerment, willingness to interact, and seeking help. SEM revealed that the increase in knowledge was significantly associated with the General attitudes toward people with mental illness construct that, in turn, was positively associated with willingness to interact and seeking help. Results encourage the use of anti-stigma interventions in order to decrease negative attitudes toward mental illness and improve behavioral intentions among students.